Establishing a Theoretical Landscape for Identifying Basal Plane Active 2D Metal Borides (MBenes) toward Nitrogen Electroreduction. (11th November 2020) - Guo, Xiangyu; Lin, Shiru; Gu, Jinxing; Zhang, Shengli; Chen, Zhongfang; Huang, Shiping
Abstract: To achieve efficient ammonia synthesis via electrochemical nitrogen reduction reaction (NRR), a qualified catalyst should have both high specific activity and large active surface area. However, integrating these two merits into one single material remains a big challenge due to the difficulty in balancing multiple reaction intermediates. Here, it is demonstrated that the boron‐analogues of MXenes, namely "MBenes", could cope with the challenge and achieve the high activity and large reaction region simultaneously toward NRR. Using extensive density functional theory computations and taking 16 MBenes as representatives, it is identified that seven MBenes (CrB, MoB, WB, Mo2 B, V3 B4, CrMnB2, and CrFeB2 ) not only have intrinsic basal plane activity for NRR with limiting potentials ranging from −0.22 to −0.82 V, but also possess superior capability of suppressing the competitive hydrogen evolution reaction. Particularly, different from the MXenes whose surface oxidation may block the active sites, once oxidized, these MBenes can catalyze NRR via the self‐activating process, reducing O*/OH* into H2 O* under reaction conditions, and favoring the N2 electroreduction. As a result, the exceptional activity and selectivity, high active area (≈10 19 m −2 ), and antioxidation nature render these MBenes as pH‐universal catalysts for NH3 production without introducing any dopants and defects. Abstract : A class of stable two‐dimensional metal borides, namely "MBenes", are demonstrated to have intrinsic basal plane activity and selectivity toward the nitrogen reduction reaction without introducing any dopants and defects. Particularly, some MBenes can prevent the active site blockage problem via the so‐called "self‐activating process", reducing O*/OH* into H2 O* under reaction conditions, and thus favoring the N2 electroreduction.